1963
DOI: 10.1038/bjc.1963.12
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity of 2-Naphthylhydroxylamine and 2-Naphthylamine

Abstract: THE discovery of the N-hydroxylation of 2-acetamidofluorene in vivo (Cramer, Miller and Miller, 1959) had been followed by recognition that 4-acetamidobiphenyl (Miller, Wyatt, Miller and Hartman, 1961b) and 2-naphthylamine (Boyland, Manson and Nery, 1960;Troll and Nelson, 1961) are metabolised by similar routes. The carcinogenic aromatic amines are also metabolised to ortho aminophenols, some of which have been shown to be carcinogenic by the technique of bladder pellet implantation in mice (Bonser, Bradshaw,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
2

Year Published

1963
1963
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 9 publications
0
13
0
2
Order By: Relevance
“…None were found in a group of 74 mice implanted with 2-naphthylamine/stearic acid pellets. Intraperitoneal injections of 2-naphthylhydroxylamine induced abdominal tumours in nine out of fifteen rats, while only two of fourteen rats developed sarcomas following similar treatment with 2-naphthylamine (Boyland, Dukes and Grover, 1963).…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…None were found in a group of 74 mice implanted with 2-naphthylamine/stearic acid pellets. Intraperitoneal injections of 2-naphthylhydroxylamine induced abdominal tumours in nine out of fifteen rats, while only two of fourteen rats developed sarcomas following similar treatment with 2-naphthylamine (Boyland, Dukes and Grover, 1963).…”
Section: Methodsmentioning
confidence: 91%
“…Clayson (1953) suggested that the aromatic amines were carcinogenic because of their conversion to ortho-hydroxylamines. Some of these compounds were shown to be carcinogenic by the technique of bladder pellet implantation in mice (Bonser, Bradshaw, Clayson and Jull, 1956), but 2-naphthylhydroxylamine, a metabolite formed by N-hydroxylation (Boyland, Manson and Nery, 1960), has induced a higher incidence of bladder tumours than any other compound tested (Bonser et al, 1963). More than half of 66 mice implanted with pellets of 2-naphthylhydroxylamine mixed with stearic acid developed bladder tumours.…”
Section: Methodsmentioning
confidence: 99%
“…The steppe lemming (Lagarus lagarus, Pall) has been recently introduced into cancer research (Pogosianz, Bolonina and Olshevskaja, 1960).This species was found useful in studies of skin cancer induction with certain polynuclear aromatic hydrocarbons and for transplantation experiments.Recent developments with carcinogenic aromatic amine derivatives have suggested that this class of compounds requires metabolic activation by hydroxylation on the nitrogen (Boyland, Dukes and Grover, 1963;Cramer, Miller and Miller, 1960; Heringlake, Kiese, Renner and Wenz, 1960;Irving, 1964;Miller, Cramer and Miller, 1960; Uehleke, 1964). In order to investigate their potential susceptibility to such chemicals, we determined whether steppe lemmings metabolized 2-acetamidofluorene (AAF) by N-hydroxylation, a reaction performed by a sensitive but not by a resistant species Weisburger et al, 1964a).…”
mentioning
confidence: 99%
“…in oil) twice weekly for three months (Boyland, Dukes and Grover, 1961). Thirteen bladder carcinomas were found among 62 surviving mice following bladder implantation of crushed paraffin wax pellets containing 2-naphthylhydroxylamine (Bonser et al, 1963).…”
mentioning
confidence: 99%